Outcome priorities for older persons with sarcopenia: brief report - Hiligsmann, Mickael; Beaudart, Charlotte; Bruyère, Olivier; Biver, Emmanuel; Bauer, Jürgen M.; Cruz-Jentoft, Alfonso J.; Gesmundo, Antonella; Goisser, Sabine; Landi, Francesco; Locquet, Médéa; Maggi, Stefania; Rizzoli, Rene; et al. (Journal of the American Medical Directors Association, 2020)
Objectives - To evaluate patients’ preferences for sarcopenia outcomes. - Design - Discrete-choice experiment (DCE) - Setting and Participants - Community-dwelling individuals older than 65 years suffering from sarcopenia recruited in Belgium, France, Germany, Italy, Spain, and Switzerland, who visited the clinic and were cognitively able to understand and fill out the survey. - Methods - In the DCE survey, participants were repetitively asked to choose which one of the 2 patients suffering from sarcopenia deserves treatment the most. The 2 patients presented different levels of risk for 5 preselected sarcopenia outcomes: quality of life, mobility, domestic activities, fatigue, and falls. The DCE included 12 choice sets. Mixed logit panel model was used to estimate patients’ preferences and latent class model was conducted to identify profiles of responses. - Results - A total of 216 sarcopenic persons were included for the analysis (68% women; mean age 78 years). All 5 preselected sarcopenia outcomes were shown to be significant. Overall, the most important sarcopenia outcome was mobility (30%), followed by the ability to manage domestic activities (22%), the risk of falls (18%), fatigue (17%), and quality of life (14%). The latent class model identified 2 classes of respondents. In the first class (probability of 56%), participants valued mobility the most (42%), followed by the ability to manage domestic activities (23%) and risk of falls (17%). In the second class, fatigue was the most important outcome (27%) followed by domestic activities (19%) and risk of falls (19%). No statistically significant associations between the latent classes and sociodemographic characteristics were found. - Conclusions and Implications - This study suggests that all 5 preselected outcomes were important for sarcopenic older individuals. Overall, the most important outcomes were mobility and the ability to manage domestic activities, although variations in preferences were observed between respondents. This could help in incorporating patient preferences when designing appropriate solutions for individuals with sarcopenia.
Available online 28 October 2019
Gesehen am 11.05.2020